Peningkatan Semangat Belajar Anak Usia Dini Melalui Sinau Bareng di Dusun Besuk-Desa Lemujut - Faldy Karno; Ismawandi Bripandika Putra; Karina Putri Pramesti; Niken Ayu Ambarwati; Noer Rahma Afifa Putri; Reni Citra Dewi; Kurnia Trisna Mauludiyah (Prioritas: Jurnal Pengabdian Kepada Masyarakat, 2023)
The KKN program in Besuk Hamlet, Lemujut Village is a non-formal education initiative which aims to increase the enthusiasm for learning of young children and involve the active participation of the local community. Through a structured step-by-step approach, this program succeeded in achieving significant positive impacts. It was found that there was a high level of enthusiasm from children and villagers, as well as active support from parents. The Sinau Bareng program has been successful in providing concrete assistance in understanding various subjects, with a focus on developing social skills, art and creativity. Apart from increasing children's enthusiasm for learning, this program also strengthens community participation in children's education. Through a collaborative approach, an environment is created that supports the sharing of knowledge and experience, strengthening social ties within the community. In conclusion, the KKN program in Lemujut Village is an example of the success of non-formal education which improves the welfare of early childhood education. This illustrates the great potential of inclusive and community-based education in improving the quality of education at the village level and strengthening social ties. In the context of Indonesian education, this initiative is an important effort to create an intelligent, wise and responsible generation, ready to face the future with confidence.